Exploring students’ experiences and perceptions in adapting folk tales into picture books within multiliteracies pedagogy - Mandarani, Vidya; Fediyanto, Niko; Talshyn, Alshynbayeva; Utari, Meralda Dwi (Universitas Islam Malang, 2025)
Although folk tales are central to the nation’s cultural heritage, their potential in English language education is often overlooked due to the dominance of traditional literacy practices and limited multimodal learning. Implementing multiliteracies pedagogy also remains underexplored. This study explores how adapting folk tales into English-language picture books within a multiliteracies framework can enrich university-level EFL pedagogy. Moving beyond translation, this approach encourages students to critically reflect on cultural narratives while expressing them creatively through multimodal design. The project involved thirty-six seventh-semester students in a Literature in ELT course. It was structured around the four pedagogical stages of the multiliteracies framework: Situated Practice, Overt Instruction, Critical Framing, and Transformed Practice. Using a qualitative content analysis design, researchers collected data through classroom observations, field notes, group discussions, student projects, and interviews. Findings show that students critically engage with folk tales’ sociocultural, moral, and symbolic dimensions. They reinterpreted these stories for new audiences, balancing creative adaptation with cultural authenticity. This process enhanced their multimodal composition skills, textual analysis, and audience awareness while strengthening their confidence and voice as future educators. The study highlights the value of integrating folk tales and multimodal practices in EFL settings to promote critical thinking, intercultural competence, and pedagogical creativity. Students showed a greater sense of identity formation through the project, emphasizing the transformative impact of culturally responsive, student-centered pedagogies. This study recommends future research to explore applying student-generated picture books in a real classroom with supporting pedagogical variables to evaluate their impact on long-term literacy development.